(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The objective of the current research is to (evaluate the content of the mathematics textbook for the fifth grade of elementary school according to the (4MAT) model for learning styles). To achieve this goal, the researcher asked the following questions:The first question: What are the criteria for learning styles according to the (4MAT) model that should be available in the content of mathematics books prescribed for the primary stage?The second question: What is the availability of (4MAT) model criteria for learning styles in the content of the mathematics textbook for the fifth grade of primary school?In order to verify the research objective, the researcher followed the analytical descriptive approach, as the research sample is from the content of the mathematics book prescribed for the fifth grade of primary school by the Iraqi Ministry of Education for the academic year (2021-2022 AD), where the researcher relied on the research tool represented by the list of (4MAT) model criteria for learning styles according to McCarthy, 1990)) for the purpose of using it in analyzing the content of the mathematics book for the fifth grade of primary school, and making sure of its validity after presenting it to a group of specialized arbitrators, as it obtained an agreement rate of (87%). After using the research tool in analyzing the content of the mathematics textbook for the fifth grade of primary school, the content analysis card was formed according to the criteria of the (4MAT) model for learning styles in its final form from four patterns, which are: (imaginative and includes one main criterion and (13) indicators, and analytical and includes a criterion One main criterion and (10) indicators, the logical one, which includes one main criterion and (16) indicators, and the dynamic one, which includes one main criterion and (12) indicators). The mathematics book for the fifth grade of primary school was analyzed according to these standards, and a sample of the analysis sample was presented to a number of specialized arbitrators, and they agreed on the validity of the analysis process. The use of other analysts and obtained an agreement ratio between analysts (0.92) using the Holsty equation. The research results revealed that: The analytical style achieved the first rank with a rate of (41.12%), and the imaginary style came in the second place with a percentage of (21.65%), while the dynamic style came in the third place with a percentage of (19.95%), and the logical style came in the last place with a percentage of (17.27%). ) in the content of the mathematics textbook for the fifth grade of primary school, and when comparing the four learning styles with the ratio agreed upon by the arbitrators and specialists, all of them came with a weak evaluation level. Based on the research results, a number of recommendations and proposals were presented.